Channel management 1 - Dent, Julian (Henry Stewart Talks, 2012)
The role and importance of channel management, A framework for channel management, Channel strategy, Market space definition, Role of the channel, Rules of engagement, Segmenting the market, The channel's role in delivering the customer proposition, Customer value propositions, Demand generation & fulfilment, Channel capabilities, Channel ecosystem mapping